Solid phase chemistry to covalently and reversibly capture thiolated RNA - Duffy, Erin E; Canzio, Daniele; Maniatis, Tom; Simon, Matthew D (Nucleic acids research, 2018)
Abstract Here, we describe an approach to enrich newly transcribed RNAs from primary mouse neurons using 4-thiouridine (s4U) metabolic labeling and solid phase chemistry. This one-step enrichment procedure captures s4U-RNA by using highly efficient methane thiosulfonate (MTS) chemistry in an immobilized format. Like solution-based methods, this solid-phase enrichment can distinguish mature RNAs (mRNA) with differential stability, and can be used to reveal transient RNAs such as enhancer RNAs (eRNAs) and primary microRNAs (pri-miRNAs) from short metabolic labeling. Most importantly, the efficiency of this solid-phase chemistry made possible the first large scale measurements of RNA polymerase II (RNAPII) elongation rates in mouse cortical neurons. Thus, our approach provides the means to study regulation of RNA metabolism in specific tissue contexts as a means to better understand gene expression in vivo.